2002
DOI: 10.1021/ja012364c
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Capillary Electrophoresis of Carbon Nanotubes

Abstract: Purification of single-walled carbon nanotubes by capillary electrophoresis (CE) is demonstrated. Real-time Raman spectroscopy of the separation process and single-wavelength UV/vis detection show the ability of CE to provide high-resolution separations of nanotube fractions with baseline separation. AFM images of collected fractions demonstrate that separations are based on tube length. The separation method is suggested to be based on alignment of the nanotubes along the separation field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 33 publications
(54 reference statements)
6
126
2
Order By: Relevance
“…29 The CE of the reaction mixtures at different reaction times showed that the charge/size ratio of the species changed over time (see Fig. 4).…”
Section: Resultsmentioning
confidence: 95%
“…29 The CE of the reaction mixtures at different reaction times showed that the charge/size ratio of the species changed over time (see Fig. 4).…”
Section: Resultsmentioning
confidence: 95%
“…Large aggregate spikes continue to be observed in the region containing primarily small to moderate-sized aggregates, whereas these smaller aggregates continue to appear as spikes throughout the region containing primarily isolated individual nanotubes. The potential for such overlapping behaviors was recognized in the original work on length-dependent separations 16 and will be an important problem to overcome in future CE work on carbon nanotubes. …”
Section: Discussionmentioning
confidence: 99%
“…53,58,[67][68][69] It should be noted that most current techniques do not begin to address the purification of carbon nanotubes by length, diameter, and chirality, although this will clearly be of great future importance. [70][71][72] …”
Section: Electronic Structure and Chemical Reactivitymentioning
confidence: 99%